Formation of a creative hub and channeling patterns for creative economy actors in the city of South Tangerang using SWOT - Susanto, Sugeng (Digital Business: Tren Bisnis Masa Depan, 2024)
The formation of a Creative Hub and Channeling Pattern for Creative Economy Actors in South Tangerang City is to formulate a form of creative hub and channeling pattern for creative economy actors as a forum for collaboration in a joint commitment effort from both the Government, Stakeholders and Creative Economy Actors to improve the economy in the people of South Tangerang City. This research was carried out using SWOT analysis, namely a strategic planning method used to evaluate strengths, weaknesses, opportunities and threats in a project or business speculation. In the results of the SWOT analysis of the Culinary Sub-Sector SWOT, the Interior Design Sub-Sector SWOT and the Music Sub-Sector SWOT provide several recommendations for the formation of a Creative Hub and Channeling Patterns for Creative Economy Actors, including establishing a culinary core community as a channel for creative hub information, establishing a management training program in design. interior, Establishing a training program for the development of the music sub sector by supporting music promotion in the creative hub.